Temporal changes in the urban system in South Korea - Chun, Yongwan; Kim, Kamyoung (Frontiers in Sustainable Cities, 2022)
South Korea has experienced a dramatic economic change since the Korean War. Its economic structure has developed from one with a primary industry-centric in the 1950s to a manufacturing or service-centric structure. The economic development has been accompanied by a steady growth of population specifically in urban areas. In addition, economic development also has triggered changes in its population distribution and, ultimately, its urban system. The purpose of this paper is to investigate changes in the urban system in South Korea using two approaches, which are primacy indices and spatial interaction indices. While the primacy indices focus on the population sizes of cities, an investigation with spatial interaction allows an examination of linkages among cities. The results show that the Korean urban system had a primacy structure in which Seoul dominates until the 1990s, after which this primacy structure of the city weakened. The spatial interaction patterns show that many cities have developed in large metropolitan areas and are highly interconnected with each other. But this new development has dominantly occurred still in the Seoul metropolitan area. These results present that urban developments have been highly concentrated in peripheral areas of Seoul that are still in the Seoul metropolitan area, with the dominance of the metropolitan area getting stronger over time.